Validation of a single repetition test to measure swimming power - Greenshields, J. T.; Skutnik, B. C.; Stickels, C. M.; Yildirim, A.; Shen, Y.; Stager, J. M. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The purpose of this study was to evaluate a newly proposed single repetition test (SRT) for calculating maximal excess external power (Pmax) against an existent, incremental, discontinuous power testing protocol (IPT) developed by Hopper, Hadley, Piva, and Bambauer (1983). Pmax from the IPT is calculated by having swimmers complete multiple maximal efforts while attached to varying external loads. This method is highly practical in a field setting; however, it is time-consuming due to the multiple maximal bouts needed to derive Pmax. We propose a single repetition, continuous, incremental test (SRT) to measure Pmax lasting approximately 15 seconds during which the external load is linearly increased through the 22.86 m length. On two occasions separated by 14 d, elite swimmers (N = 14) performed IPT or SRT. Power delivered to an external load (Pload) during the IPT was calculated using a known force applied via a modified Power Rack® and hand-timed speed (N = 2) over a distance of 10 m. During the IPT swimmers completed multiple repetitions (6 to 10) until a maximal Pload was observed. During the SRT all data were automatically collected at 500 Hz by computer through a commercial A/D. The external load was applied using an electronically braked motor. The load was linearly increased beginning at 10 m and continuing to task failure. To test the repeatability of the calculated Pload during the SRT swimmers (n = 13) performed repeat trials. During the IPT swimmers completed 7 ± 2 trials. Maximal Pload was IPT 98.8 ± 34.3 W and SRT 110.0 ± 32.3 W. The between method correlation was 0.98 (90% CI 0.95 to 0.99), typical error expressed as a coefficient of variation 6.6% (90% Cl 5.0 to 10.2%). The SRT also showed repeatable Pload values between trials; 111.6 ± 36.9 W, 111.2 ± 36.5 W. These results were correlated 0.99 (90% Cl 0.98 ± 1.0), with within-subject variation 3.2% (90% CI 2.4 to 4.9%). The high validity and repeatability of the SRT makes the methodology useful for research, athlete assessments, or field studies involving competitive swimmers. The single bout protocol requires little time commitment from coaches, swimmers and researchers alike and may avoid invoking any significant subject fatigue.